Manhaj Al-Khash: Studi atas Tafsir Fath Al-QadirKarya Imam Al-Syaukani pada QS. Al-Hajj - Maolidya Asri Siwi Fangesty; Mochammad Ikhsan; Muhamad Hamdan Tauviqillaah; Eni Zulaiha; Wildan Taufiq; Badruzzaman M. Yunus (Institut Muslim Cendekia, 2024)
Manhaj tafsir is one aspect in the discipline of Tafsir Al-Qur'an which is used to see the tendency of a book of interpretation.This study attempts to see the tendency of the Book of Tafsir Fath Al-Qadir in QS.Al-Hajj by Imam Al-Syaukani, both in terms of its general method and its special method.This study is considered important to be carried out because it is intended to determine Al-Syaukani's tendency in interpreting the Qur'an in his tafsir work, because it is known that he came from a Shiite background.This study is a qualitative study with the presentation of descriptive analysis whose data collection uses literature studies.The author concludes that Al-Syaukani in his general method, he uses the tahlili method and predominantly uses bi al-ra'y sources, while his special method is always consistent with his eleven steps, such as presenting verses and grouping them into certain groups of verses, analyzing language, mentioning related narrations, etc. As for the alleged Shiite tendency, the author did not find it in Al-Syaukani's interpretation in QS. Al-Hajj.